Designing clinical research - Hulley, Stephen B. (Wolters Kluwer/Lippincott Williams & Wilkins, 2013)
"This book provides a practical guide to planning, tabulating, formulating, and implementing clinical research, in an easy-to-use, readable presentation"--Provided by publisher.